MALIGNANT OVARIAN GERM CELL TUMORS AT A TERTIARY CARE SETTING IN PAKISTAN - Hannan, Abdul; Malik, Mahim Akmal; Fasih, Samir; Badar, Farhana; Siddiqui, Neelam (Journal of Ayub Medical College Abbottabad, 2015)
Background: Malignant Ovarian Germ Cell Tumours (MOGCT) are rare neoplasms and their behavior is unknown in South-East Asian population. Methods: Case records of 66 patients from 1994-2007 with MOGCT were reviewed. Histology was based on WHO classification. Tumours were staged according to International Federation of Gynecology and Obstetrics (FIGO) system. Data was collected on age, histopathology, stage, alpha-feto protein (AFP) and B-human chorionic gonadotropins (B-hCG) levels, treatment, time to recurrence (TTR) and overall survival (OS). OS was the interval in months between date of diagnosis and last encounter while TTR was between the date of diagnosis and recurrence. OS was determined by Kaplan-Meier method. Results: Median age of our patients was 18 years. Ninteen patients were in stage I, eight in II, twenty-one in III and eighteen in stage IV. Histologically, dysgerminoma was the most common diagnosis (22 patients) followed by teratoma in 16, yolk sac tumor in 15, mixed germ cell tumor in 12 while embryonal carcinoma was identified in only one patient. Median followup was 48 months (0.2-183). All patients underwent initial surgery. Fertility sparing procedures were performed in 75% patients. Thirty-four patients (57.62%) achieved complete remission while 16 (27.11%) had progressive disease. Seven (10.60%) patients relapsed, all within first 3 years. TTR was 11.2-32.5 months. OS for study population was 60 months. Sixteen (88%) of stage I while only 4 (26.6%) of stage IV patients were alive at median follow-up. Conclusions: MOGCT has good prognosis with conservative surgery and platinum chemotherapy. Fertility sparing surgery has become a standard in MOGCTs, so awareness should be raised amongst professionals for early referral to cancer care facility.